Workshop Brainstorming: Mengaktifkan Pengetahuan Awal Siswa Sebelum Memasuki Topik Diskusi - Mikhael Misa; Hesni Neno (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
A brainstorming workshop is an activity to activate students' prior knowledge before entering into discussion topics. This workshop aims to provide effective instructors to engage and awaken students' prior knowledge and experiences. This workshop is based on the idea that students must have prior knowledge of a topic before entering into a topic of discussion. The aim of this workshop is to provide facilitators who can engage students in the process of activating their prior knowledge. Participants who attended this workshop totaled 59 people consisting of 30 students in semester 6A and 29 students in semester 6B who were prospective participants in the Field Experience Practice (PPL). The results obtained were that most of the students felt very satisfied, satisfied, and quite satisfied because they had good knowledge and competence after participating in student prior knowledge activation workshops, before entering into discussion topics in the teaching and learning process. This workshop is very useful for students, especially teaching practice in the field. And through this workshop, you can improve the abilities that students currently have, which can be applied in schools where they practice.